The Matthew effect, research productivity, and the dynamic allocation of NIH grants. - Qiu, Y. J. Jeff (RAND Journal of Economics (Wiley-Blackwell), 2023)
Funding is important for research. However, research funding may suffer from the Matthew effect: the more researchers already have, the more they will be given. I develop an empirical framework to study how the National Institutes of Health (NIH) could allocate funding in a dynamically optimal manner by balancing funds between young and veteran principal investigators (PIs). I find that the discount factor that rationalizes NIH's funding behavior is about 0.75, implying it may underfund young PIs. Moreover, a temporary funding cut would have long‐lasting effects on overall research output through its adverse impact on investment in young PIs.